Investigation of and mechanism proposal for solvothermal reaction between sodium and 1-(2-hydroxyethyl)piperidine as the first step towards nitrogen-doped graphenic foam synthesis. (22nd July 2020) - Moumaneix, Lilian; Parra, Jenifer Guerrero; Fontana, Sébastien; Lapicque, François; Hérold, Claire
Abstract : Solvothermal reaction involving 1-(2-hydroxyethyl)piperidine and sodium: a promising step in the synthesis of high surface area N-doped graphenic materials. Abstract : For the purpose of synthetizing 3-dimensional nitrogen-doped graphenic materials, which could be used as oxygen reduction catalysts in membrane fuel cells, a solvothermal-based route was successfully carried out. However, the solvothermal reaction between metallic sodium and 1-(2-hydroxyethyl)piperidine (HEP), with the latter as the source of both carbon and nitrogen, is still little understood. The present work was aimed at investigating the solvothermal process under different conditions of temperature and pressure and with different amounts of sodium. Use of in situ mass spectroscopy during the three-day reaction revealed the early formation of dihydrogen, as well as carbon oxides, methane and ammonia, in addition to fragments of ethylpiperidine alkoxide (EP-ONa). XRD measurements evidenced the formation of sodium-based compounds, e.g. hydride, carbonate, hydroxide, and cyanide. Interestingly, Raman spectroscopy revealed the significant presence of large aromatic molecules as well as an sp 2 carbon network, an early precursor of graphene. Analysis of the overpressures and reaction yields suggests that the primary compound from the reaction of HEP with sodium is a large sp 2 carbon-based network entrapping numerous sodium-based molecules as well as a volatile liquid phase. The suggested reaction mechanism provides information to better tailor the solvothermal products, whose pyrolysis at 850 °C led to very high specific area nitrogen-doped carbon materials.